Impact of drought stress on biochemical and molecular responses in lavender (Lavandula angustifolia Mill.): effects on essential oil composition and antibacterial activity - Hosseini, Ramin; Heidari, Mahsa (Frontiers in Plant Science, 2025)
Drought stress significantly influences the physiological, biochemical, and molecular processes in plants, directly impacting their growth and defense mechanisms. This study evaluates the response of Lavandula angustifolia (lavender) to different levels of water deficit, with field capacity (FC) treatments set at 20%, 40%, 60%, and 80%. We assessed various biochemical parameters, including protein content, chlorophyll a and b levels, flavonoid and phenolic content, and antioxidant activity, to determine how drought stress affects lavender’s primary and secondary metabolism. As water availability decreased, we observed a reduction in total protein and chlorophyll content, while the highest levels of flavonoids, phenolics, and antioxidant activity were recorded in control plants at 80% FC. Gene expression analysis of key terpene synthase genes revealed differential expression patterns, with linalool synthase and α-pinene synthase peaking at 40% FC, and 1,8-cineole synthase and β-phellandrene synthase reaching their highest activity under severe drought (20% FC). Despite this, a clear correlation between gene expression and metabolite accumulation in essential oils was not observed. Drought-induced changes in essential oil composition were associated with enhanced antibacterial activity, particularly against foodborne Gram-positive and Gram-negative bacteria, suggesting that water stress can modulate the therapeutic potential of lavender oil.